If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6)(x + 9) = 2x Reorder the terms: (-6 + x)(x + 9) = 2x Reorder the terms: (-6 + x)(9 + x) = 2x Multiply (-6 + x) * (9 + x) (-6(9 + x) + x(9 + x)) = 2x ((9 * -6 + x * -6) + x(9 + x)) = 2x ((-54 + -6x) + x(9 + x)) = 2x (-54 + -6x + (9 * x + x * x)) = 2x (-54 + -6x + (9x + x2)) = 2x Combine like terms: -6x + 9x = 3x (-54 + 3x + x2) = 2x Solving -54 + 3x + x2 = 2x Solving for variable 'x'. Reorder the terms: -54 + 3x + -2x + x2 = 2x + -2x Combine like terms: 3x + -2x = 1x -54 + 1x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 -54 + 1x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '54' to each side of the equation. -54 + 1x + 54 + x2 = 0 + 54 Reorder the terms: -54 + 54 + 1x + x2 = 0 + 54 Combine like terms: -54 + 54 = 0 0 + 1x + x2 = 0 + 54 1x + x2 = 0 + 54 Combine like terms: 0 + 54 = 54 1x + x2 = 54 The x term is 1x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 54 + 0.25 Reorder the terms: 0.25 + x + x2 = 54 + 0.25 Combine like terms: 54 + 0.25 = 54.25 0.25 + x + x2 = 54.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 54.25 Calculate the square root of the right side: 7.365459931 Break this problem into two subproblems by setting (x + 0.5) equal to 7.365459931 and -7.365459931.Subproblem 1
x + 0.5 = 7.365459931 Simplifying x + 0.5 = 7.365459931 Reorder the terms: 0.5 + x = 7.365459931 Solving 0.5 + x = 7.365459931 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 7.365459931 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 7.365459931 + -0.5 x = 7.365459931 + -0.5 Combine like terms: 7.365459931 + -0.5 = 6.865459931 x = 6.865459931 Simplifying x = 6.865459931Subproblem 2
x + 0.5 = -7.365459931 Simplifying x + 0.5 = -7.365459931 Reorder the terms: 0.5 + x = -7.365459931 Solving 0.5 + x = -7.365459931 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -7.365459931 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -7.365459931 + -0.5 x = -7.365459931 + -0.5 Combine like terms: -7.365459931 + -0.5 = -7.865459931 x = -7.865459931 Simplifying x = -7.865459931Solution
The solution to the problem is based on the solutions from the subproblems. x = {6.865459931, -7.865459931}
| X^2+6x+8=0 | | A=zw+z | | -8x^2+9x+7=0 | | p-7=3 | | mn-2p=2 | | 46x/82x | | -19/6+(-5/6) | | 21-y+4=30-6y | | 21z-39=z-(-39) | | 21z-39=z-39 | | b^3m^3-64h^3= | | (15c^-7d^3/35c^5d^7)^-3 | | 44=16+n | | 4x-x^3= | | t(5t^2+3)=0 | | 18+j=94 | | 47-4x=5x+19 | | 17x-4x^3= | | 4953=P(1+(0.03)(9)) | | 5f^12g^-4/f^5g^7 | | 25-p^2y^2= | | k-22=101 | | 2(x+Y)+6Y= | | 21(x-39)=x+39 | | 81-b^4= | | 2/49z^3+1/14z^2 | | 8p^3-h^3= | | 21(x-39)=-39-x | | -14-6X=10-10 | | q+13=112 | | 4X-7=56-3 | | (3/x-2)-(1-x/x) |